High Removal Rate Cobalt Slurry with Glutathione on Chemical Mechanical Polishing in Alkaline Slurry. (10th September 2020) - Xu, Aoxue; Feng, Daohuan; Wang, Weilei; Liu, Weili; Song, Zhitang
Abstract : As the technology node reaches 10 nm and below, cobalt has great potential as a barrier layer for copper interconnects and even as a new generation of interconnect materials. In this paper, the effect of double complexation of L-Aspartic Acid (L-Asp) and glutathione (GSH) on cobalt chemical mechanical polishing (CMP) is investigated in H2 O2 based alkaline slurry. The results reveal that L-Asp and GSH can respectively complex cobalt ions to form a water-soluble complexes and cobalt removal rate increased more than ten times to 2500 Å min −1 . Through electrochemical tests and X-ray photoelectron spectroscopy (XPS) experiments to explore the removal mechanism of cobalt. The analysis results indicate that the increase in the removal rate of cobalt is due to the formation of Co-L-Asp complexes and Co(II)-GSH complexes and Co(III)-GSH complexes on the cobalt surface. In addition, adding GSH on the basis of L-Asp and H2 O2 can effectively reduce the potential difference between copper and cobalt.